Áreas verdes e o índice de áreas verdes públicas de Uberlândia/MG por setores - Toledo, Fabiane dos Santos (2012)
This work has quantified and qualified the green areas in the city of Uberlândia/MG stablishing the ratio of green areas per urban sectors, expressed by the square footage of public use open spaces related to the total number of inhabitants. Firstly, the areas were requantified, in the categories of parks and squares, and associated with the urban sectors – integrated neighborhoods, and calculated the individual ratio of green areas. By the use of interaction matrices grounded on the more relevant concepts for this study, the sampling areas were analyzed and qualified identifying their influences on the environmental quality content. Emphasizing that these areas offer chances of leisure, recreation and life quality and effectivate the conservation and preservation of these sites, were found and stablished possible strategies of positive application in public areas with the objective of improving aspects of environmental quality and life quality of the population of Uberlândia.